Discovery of novel anelloviruses in small mammals expands the host range and diversity of the Anelloviridae - Souza, William Marciel de (2018)
The Anelloviridae comprises single-stranded DNA viruses currently grouped in sixty-eight species classified in twelve genera. They have been found in many vertebrate hosts including primates. In this study, we describe the application of the high-throughput sequencing to examine the frequency and diversity of anelloviruses in rodents, bats and opossums captured in Sao Paulo State, Brazil. We report a total of twenty-six anelloviruses with sixteen nearly complete genomes and ten partial genomes, which include eleven potential novel species identified in rodents (Cricetidae), bats (Molossidae and Phyllostomidae), and opossums (Didelphidae). We also propose the inclusion of two potential new genera within the Anelloviridae family, provisionally named Omegatorquevirus and Sigmatorquevirus, including six and three novel species of anelloviruses, respectively. In summary, this study expands the diversity and the host range of the known anelloviruses.